Using e-Services in Slovak Criminal Proceedings - KLÁTIK, Jaroslav; VAŠKO, Adrián (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020DO - 10.14505/jarle.v11.3(49).23, 2020)
This paper provides an overview of the development of electronic justice services. Approximately € 112 million has been invested in information and communication technologies in the judiciary over the past five years, mainly from EU funds. These investments bring significant progress in speeding up and streamlining the judicial system in the Slovak Republic. This work was supported by the Slovak Research and Development Agency under the contract No. APVV-15-0437.